Case Report: Acute Necrotizing Encephalopathy Following COVID-19 Vaccine - Bensaidane, Mohamed Reda; Picher-Martel, Vincent; Émond, François; De Serres, Gaston; Dupré, Nicolas; Beauchemin, Philippe (Frontiers in Neurology, 2022)
OBJECTIVES: Acute Necrotizing Encephalopathy (ANE) is a rare neurological disorder arising from a para or postinfectious “cytokine storm”. It has recently been reported in association with COVID-19 infections. METHODS: A 56-year-old male with a diagnosis of ANE 48 hours following a first dose of ChAdOx1 nCoV-19 vaccination was investigated. Cytokine analyses on serum and cerebrospinal fluid (CSF) were performed. The patient was treated with high-dose corticosteroids and followed clinically and radiologically. RESULTS: Favourable clinical and radiological outcome were noted. There was upregulation in serum levels of CXCL5, CXCL1, Il-8, IL-15, CCL2, TGF-B and EGF, and up-regulation in CSF levels of CXCL5, IL-2, IL-3 and IL-8. DISCUSSION: As COVID-19 infection has been previously reported as a possible rare cause of ANE, we speculate on an aberrant immune response mechanism that was brought on by the vaccine. To increase our understanding of the pathogenesis of ANE in the context of COVID-19 vaccination, and to better define its clinical features and outcomes, clinicians and scientists should continue reporting convincing cases of such entities.